2019
DOI: 10.3390/ijerph16193583
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Escherichia coli, Klebsiella pneumoniae and Staphylococcus spp. in Houseflies and Blowflies from Farms and Their Environmental Settings

Abstract: Background: Antimicrobial resistance is rising globally at an alarming rate. While multiple active surveillance programs have been established to monitor the antimicrobial resistance, studies on the environmental link to antimicrobial spread are lacking. Methods: A total of 493 flies were trapped from a dairy unit, a dog kennel, a poultry farm, a beef cattle unit, an urban trash facility and an urban downtown area to isolate Escherichia coli, Klebsiella pneumoniae and Staphylococcus spp. for antimicrobial susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 24 publications
5
32
0
Order By: Relevance
“…This finding is an indicator for the limited options of appropriate antibiotic therapy regimen for ESBL-producing bacterial infection management. Poudel et al [ 20 ] also reported high rates of resistance of E. coli and K. pneumoniae isolated from flies against tetracycline and ampicillin due to emergence of ESBL-producing strains. This might probably be caused by plasmid-mediated mobile resistance genes such as quinolone-resistance (qn r) genes, aminoglycoside acetyltransferase ( aac ), dfr (trimethoprim resistance) and sul (sulfamethoxazole resistance) genes, being more frequent in ESBL-producing bacteria compared to ESBL-negative bacteria [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is an indicator for the limited options of appropriate antibiotic therapy regimen for ESBL-producing bacterial infection management. Poudel et al [ 20 ] also reported high rates of resistance of E. coli and K. pneumoniae isolated from flies against tetracycline and ampicillin due to emergence of ESBL-producing strains. This might probably be caused by plasmid-mediated mobile resistance genes such as quinolone-resistance (qn r) genes, aminoglycoside acetyltransferase ( aac ), dfr (trimethoprim resistance) and sul (sulfamethoxazole resistance) genes, being more frequent in ESBL-producing bacteria compared to ESBL-negative bacteria [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to inhibit further expansions of ESBL-carrying bacteria from hospitals to residential areas, environmental and health professionals and municipality administration should work together and strengthen a one health approach. Future AMR prevention and control protocols may consider screening of flies for AMR and eradication-measures to control the population density of flies at health care facilities in tropical regions [ 20 ]. As distribution of ESBL genes in clinical samples and flies caught in the hospital show comparable results, flies might be used as an indicator organism for ESBL-prevalence in hospital facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This nding is an indicator for the limited options of appropriate antibiotic therapy regimen for ESBL-producing bacterial infection management. Poudel A, et al (2019) also reported high rates of resistance of E. coli and K. pneumoniae isolated from ies against tetracycline and ampicillin due to emergence of ESBL-producing strains (21). This might probably be caused by plasmidmediated mobile resistance genes such as quinolone-resistance (qnr) genes, aminoglycoside acetyltransferase (aac), dfr (trimethoprim resistance) and sul (sulfamethoxazole resistance) genes, being more frequent in ESBL-producing bacteria compared to ESBL-negative bacteria (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…In order to inhibit further expansions of ESBL-carrying bacteria from hospitals to residential areas, environmental and health professionals and municipality administration should work together and strengthen a one health approach. Future AMR prevention and control protocols may consider screening of house ies for AMR and eradication-measures to control the population density of house ies at health care facilities in tropical regions (21). As distribution of ESBL genes in clinical samples and house ies caught in the hospital show comparable results, house ies might be used as an indicator organism for ESBL-prevalence in hospital facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This nding is an indicator for the limited options of appropriate antibiotic therapy regimen for ESBL-producing bacterial infection management. Poudel et al (2019) also reported high rates of resistance of E. coli and K. pneumoniae isolated from ies against tetracycline and ampicillin due to emergence of ESBL-producing strains (21). This might probably be caused by plasmidmediated mobile resistance genes such as quinolone-resistance (qnr) genes, aminoglycoside acetyltransferase (aac), dfr (trimethoprim resistance) and sul (sulfamethoxazole resistance) genes, being more frequent in ESBL-producing bacteria compared to ESBL-negative bacteria (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%